PENGARUH MINAT BACA BUKU BERBAHASA INGGRIS TERHADAP TINGKAT INTELEKTUAL PASIS DIKREG SESKOAL TP.2019 - Yan Edward Saragih (Universitas 17 Agustus 1945 Surabaya, 2019)
This article discusses a study on the impact of interest in reading academic reference and intellectual level in the Indonesian Navy educational institution. The Navy has a vision to create a world class organization capable of carrying out the defence of Matra Sea. The role of quality human resources becomes a major factor in carrying out assignments. Seskoal as an educational institution of the Navy has the main task of implementing the highest general development education in the Navy, which contributes to improving intellectual level for each of its graduates. The importance of fostering interest in reading English-language reference books and academic culture implementation needs to be realized in connection student officers Dikreg is implementing educational task. The close relationship between the educational process, institutions and student officers a positive impact on meeting the educational goals expected. Based on this background, this study purports to measure how much influence the interest in reading English-language reference books and academic culture on an intellectual level pasis Dikreg Seskoal TP.2019. In this study using quantitative research methods pasis population Dikreg TP. 2019 one hundred and fifty people. The next step to implement the deployment of questionnaires, interviews and data processing using SPSS version 25.